Studi Fenomenologi Penyelarasan Makna dan Pengalaman Penikmat Warung Kopi di Ambon - Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
Indonesia is one of the largest coffee producing countries in the world. Coffee plants themselves are not native to Indonesia, coffee was brought in by the Dutch during colonial times, since then coffee has become part of the culture and habits of the Indonesian people. Lately the trend of drinking coffee has begun to return to popularity. This can be seen from the large number of coffee shops that have emerged. The trend of drinking coffee and coffee shops also reaches Ambon. Coffee shops in Ambon are also a symbol of peace, that in coffee shops all groups are free to gather. This study examines intercultural communication that occurs in coffee shops in Ambon, and aim to describe how actors involved in communication create their social reality. The study elaborate CMM (Co-Ordinated Management of Meaning) theory and conducted using qualitative methods, with a phenomenological approach. The research data was obtained through in-depth interviews with speakers and also observation and literature review. The results of the study show that the consequences of the conflict in the coffee shop are distinguished by region, Islam and Christianity, so that visitors also become separated between groups. Communication occurs between actors in one group, both between owners and visitors who are in the same category. Different of communication can be seen verbally and non-verbally. Indonesia merupakan salah satu negara produsen kopi terbesar di dunia. Tanaman kopi sendiri bukan tanaman asli Indonesia, kopi dibawa masuk oleh Belanda pada masa penjajahan, mulai sejak itu meminum kopi telah menjadi bagian dari budaya dan kebiasaan masyarakat Indonesia. Belakangan ini trend minum kopi mulai kembali popular. Hal ini dapat dilihat dari banyak jumlah warung kopi yang muncul. Trend minum kopi dan warung kopi ini juga sampai ke Ambon. Warung kopi di Ambon juga merupakan simbol dari perdamaian, bahwa dalam warung kopi semua kelompok bebas berkumpul. Penelitian ini mengkaji komunikasi antar budaya yang terjadi dalam warung kopi di Ambon, serta bertujuan untuk mendeskripsikan bagaimana aktor yang terlibat komunikasi menciptakan realitas sosialnya. Penelitian mengelaborasi teori CMM (Co-Ordinated Management of Meaning) dan menggunakan metode kualitatif, dengan pendekatan fenomenologi. Data penelitian diperoleh melalui wawancara mendalam dengan narasumber dan juga observasi serta kajian pustaka. Hasil dari penelitian menunjukkan akibat dari konflik warung kopi dibedakan berdasarkan wilayahnya, Islam dan Kristen, sehingga pengunjung juga menjadi terpisah antar kelompok. Komunikasi terjadi antar aktor dalam satu kelompok, baik antara pemilik dengan pengunjung yang sama-sama dalam kategori satu kelompok. Perbedaan komunikasi dapat terlihat secara verbal dan non-verbal.